A case of multiple inflammatory hepatic pseudotumor protruding from the liver surface after colonic cancer. (2017) - Nitta, Toshikatsu; Kataoka, Jun; Inoue, Yoshihiro; Fujii, Kensuke; Ohta, Masahito; Kawasaki, Hiroshi; Takeshita, Atsushi; Ishibashi, Takashi
Highlights: IHPT is difficult to distinguish from malignant tumors Knowledge of IHPT is necessary to allow for treatment, even without experience. Abstract: Introduction: Inflammatory hepatic pseudotumor (IHPT) is an important benign liver disease because it is difficult to clinically and radiologically distinguish from malignant tumors. Presentation of case: Here, we describea case of a 67-year-old male patient diagnosed with multiple inflammatory hepatic pseudotumors. The patient had undergone left hemicolectomy for descending colonic cancer (T3 N0 M0 stage IIA) 2 years prior. He underwent segment 6 and segment 7 partial hepatectomy because of suspected liver metastasis. The patient had an unremarkable postoperative course and was discharged 7 days after surgery. Marked infiltration of inflammatory cells was observed on histological examination. The patient was finally diagnosed with IHPT of the fibrohistiocytic type. Discussion: Repeated imaging studies over 1 month showed the spontaneous regression of the hepatic tumors. Therefore, knowledge regarding this condition is necessary to allow for treatment, even in the absence of experience. During examination, it may be important to ascertain lesion size. Moreover, percutaneous needle biopsy and follow-up examinations are necessary for cases of suspected IHPT. Conclusion: Hepatectomy should be considered if the lesion is suspected to be an IHPT.